2007
DOI: 10.3382/ps.2007-00233
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetic Diversity and Population Structure for Commercial Chicken Lines Based on Forty Microsatellite Analyses

Abstract: The aims of the current study were to assess genetic diversity, conduct genetic characterization, and evaluate usefulness of an individual assignment test for 12 commercial chicken lines using 40 microsatellite markers. A total of 268 distinct alleles were observed across the 12 lines, and 42 of the 268 alleles (15.7%) were unique to only 1 line. Mean observed heterozygosity within a line ranged from 0.295 to 0.664, and the highest value was obtained from 1 of the White Plymouth Rock lines. Significant deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 20 publications
10
40
4
2
Order By: Relevance
“…CLEMENTINO et al (2010) andFONTEQUE et al (2014) found an average number of 9.6 and 12.4 alleles per locus, respectively, in studies with microsatellites in free range chickens from Brazil. Lower values than the results found in this study were also described by AL-QAMASHOUI et al (2014) - 8.4 (VANHALA et al, 1998;KYSER et al, 2000;ZHANG et al, 2002;HILLEL et al, 2003;TADANO et al, 2007;BERTHOULY et al, 2008;ROSÁRIO et al, 2009;CHATTERJEE et al, 2010;TADANO et al, 2012;WILKINSON et al, 2012). Normally, it is expected that the genetic variability of commercial chickens lines had been reduced because they are selected for quantitative traits (HILLEL et al, 2003).…”
Section: Resultssupporting
confidence: 61%
“…CLEMENTINO et al (2010) andFONTEQUE et al (2014) found an average number of 9.6 and 12.4 alleles per locus, respectively, in studies with microsatellites in free range chickens from Brazil. Lower values than the results found in this study were also described by AL-QAMASHOUI et al (2014) - 8.4 (VANHALA et al, 1998;KYSER et al, 2000;ZHANG et al, 2002;HILLEL et al, 2003;TADANO et al, 2007;BERTHOULY et al, 2008;ROSÁRIO et al, 2009;CHATTERJEE et al, 2010;TADANO et al, 2012;WILKINSON et al, 2012). Normally, it is expected that the genetic variability of commercial chickens lines had been reduced because they are selected for quantitative traits (HILLEL et al, 2003).…”
Section: Resultssupporting
confidence: 61%
“…To commercial birds (breeds or lines) have been observed medium values of HE between 0.00 (highly inbred lines) and 0.74 and HO from 0.00 to 0.67 (Dávila et al 2009, Hillel et al 2003, Tadano et al 2007, Vanhala et al 1998, Zhang et al 2002, Zhou & Lamont 1999and Liu et al 2008. To non-commercial birds the values were from 0.56 to 0,86 (HE), and from 0.38 to 0.63 (HO) (Hillel et al 2003, Kaya et al 2008, Nasiri et al 2007, Nassiri et al 2007, Shahbazi et al 2007, Zhang et al 2002.…”
Section: Resultsmentioning
confidence: 98%
“…Kedu chickens have high genetic diversity and genetically distant from other chickens (Ismoyowati et al 2012). According to Tadono et al (2007) degradation of genetic variability is caused by maintenance in the same environments; thus, in the caracteristics of beak, wing, femur, and tibiotarsus length there is no longer any variation.…”
Section: Quantitative Characteristicsmentioning
confidence: 99%